Effects of folic acid with vitamin B12/vitamin B6 intervention on serum homocysteine metabolism and complications in patients with type 2 diabetes: a systematic review and meta-analysis of randomized controlled trials - Yin, Yaqi; Zhao, Ziming; Wang, Xu; Wu, Qibiao (Frontiers in Nutrition, 2025)
AimsFolic acid and B vitamins play key roles in regulating serum homocysteine metabolism. Elevated homocysteine levels have been associated with insulin resistance and diabetes-related complications in patients with type 2 diabetes mellitus. This study evaluated the effects of folic acid supplementation combined with B vitamins (B12 and B6) on homocysteine levels and complication risk in adults with type 2 diabetes mellitus.MethodsWe conducted a systematic search of eight databases from inception through August 30, 2025. The primary efficacy outcome was serum homocysteine level, while safety outcomes included the overall incidence and specific types of diabetes-related complications. Meta-analyses were performed using R version 4.5.0 with the meta package (version 8.1-0), employing random-effects models. Results are presented as standardized mean differences (SMDs) with 95% confidence intervals (CIs) for continuous outcomes and risk ratios (RRs) with 95% CIs for dichotomous outcomes.ResultsTwenty-nine studies met the inclusion criteria: 26 investigated folic acid plus vitamin B12, one examined folic acid plus vitamin B6, and two evaluated folic acid in combination with both vitamins B12 and B6. Supplementation with folic acid plus vitamin B12 (SMD = −2.77, 95% CI [−3.23, −2.30], P < 0.0001) significantly reduced serum homocysteine levels and decreased the incidence of total complications (RR = 0.30, 95% CI [0.24, 0.38], P < 0.0001). Similar results were also observed for specific complication subtypes.ConclusionsSupplementation with folic acid and vitamin B12 may reduce homocysteine levels and the risk of complications in patients with type 2 diabetes mellitus. The substantial heterogeneity and limited sample size of our results necessitate confirmation through additional high-quality, large-scale randomized controlled trials.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251141157.